2022
DOI: 10.1007/s00439-022-02452-x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of polygenic risk scores in genomic medicine practices: a systematic review

Abstract: Genomic medicine aims to improve health using the individual genomic data of people to inform care. While clinical utility of genomic medicine in many monogenic, Mendelian disorders is amply demonstrated, clinical utility is less evident in polygenic traits, e.g., coronary artery disease or breast cancer. Polygenic risk scores (PRS) are subsets of individual genotypes designed to capture heritability of common traits, and hence to allow the stratification of risk of the trait in a population. We systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Although many GRS have been developed and validated in the general population to predict diseases, they still face challenges including portability and interpretability before application in routine clinical care. 34 GRS could be especially useful in high-risk populations to identify individuals with . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many GRS have been developed and validated in the general population to predict diseases, they still face challenges including portability and interpretability before application in routine clinical care. 34 GRS could be especially useful in high-risk populations to identify individuals with . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…Although many GRS have been developed and validated in the general population to predict diseases, they still face challenges including portability and interpretability before application in routine clinical care. 34 GRS could be especially useful in high-risk populations to identify individuals with 12 additional high genetic risk for intervention trials. 35 Anticoagulant users are at increased ICH risk, and the additional knowledge of individual genetic ICH risk could influence clinical decision making in situations with limited evidence or equivocality of clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…11 Center for Precision Psychiatry, Massachusetts General Hospital, Boston, MA, USA. 12 Stanley Center for Psychiatric Research, Broad Institute of MIT and Harvard, Cambridge, MA, USA. 13 Channing Division of Network Medicine, Boston, MA, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…There are several known barriers to the clinical adoption of PRS, including the current limited evidence for their clinical utility, and the known differential predictive performance of the scores in different population groups [8,9]. Despite these concerns, early evidence suggests that there may be some clinical utility to sharing PRS in the preventive health setting [10][11][12]. Because we currently have very limited information about the clinical impact of sharing PRS, evidence-based guidelines supporting the use of PRS do not yet exist.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include GCTA (h 2 , Yang et al As previously shown by Daetwyler et al (2008), h 2 and p can also be used to determine how well we can predict a phenotype from using genetic variants alone. Such genetic predictors are called polygenic scores (PGS), and are getting closer to being included as part of existing clinical risk models for diseases (Torkamani et al, 2018;Lambert et al, 2019;Kumuthini et al, 2022). LDpred2 is a widely used polygenic score method that can directly build PGS using summary statistics results from genome-wide associations studies (GWAS), making it highly applicable (Privé et al, 2020b;Pain et al, 2021;Kulm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%